Positive electrode active material for secondary battery, and secondary battery

By using lithium-nickel composite oxides with different particle sizes and increasing the content of Ca and Sr, the problem of high internal resistance of lithium-ion batteries is solved, and better output characteristics and fast charging and discharge performance are achieved.

CN119866552APending Publication Date: 2025-04-22PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380064861.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-22
Filing Date
2023-08-29
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The internal resistance of existing lithium-ion batteries is relatively high, which affects its fast charging and discharging performance. The existing positive electrode active substances still have room for improvement in reducing the internal resistance of the battery.

Method used

The first lithium nickel composite oxide with a particle diameter of 8 μm or more and 30 μm or less and the second lithium nickel composite oxide with a particle diameter of 6 μm or less is used as the positive electrode active material, and the Ca and Sr contents are increased on the surface of the primary particles of the first lithium nickel composite oxide so that they are greater than or equal to the corresponding content of the second lithium nickel composite oxide.

Benefits of technology

It effectively reduces the internal resistance of the secondary battery, improves the output characteristics and fast charging and discharging performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119866552A_ABST
    Figure CN119866552A_ABST
Patent Text Reader

Abstract

A positive electrode active material for a secondary battery, which is an example of an embodiment, includes a first lithium nickel composite oxide having a volume-based D50 of 8-30 [mu] m, and a second lithium nickel composite oxide having a volume-based D50 of 6 [mu] m or less. The first lithium nickel composite oxide is a secondary particle formed by aggregating primary particles, and at least one element selected from Ca and Sr is present on the surface of the primary particles. The total content of Ca and Sr in the first lithium nickel composite oxide is greater than or equal to the total content of Ca and Sr in the second lithium nickel composite oxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a positive electrode active material and a secondary battery using the same, and in particular to a positive electrode active material suitable for a non-aqueous electrolyte secondary battery. Background Art

[0002] In recent years, secondary batteries such as lithium-ion batteries have been widely used for applications such as automotive applications and power storage applications that require high capacity, high durability, and fast charge and discharge performance. The positive electrode active material, which is the main component of the secondary battery, has a great influence on these properties, so a lot of research has been done on the positive electrode active material. For example, in Patent Document 1, as an active material for a non-aqueous electrolyte secondary battery, a lithium transition metal composite oxide with an α-NaFeO2 structure is disclosed. The composite oxide contains one or more transition metal elements selected from the group consisting of Mn, Ni and Co, and alkaline earth metals and W are present on the particle surface of the composite oxide. Patent Document 1 records: By using the composite oxide, the charge and discharge cycle characteristics of the battery are improved.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2018-129221 Summary of the invention

[0006] In secondary batteries such as lithium-ion batteries, reducing internal resistance and improving output characteristics, for example, to enhance rapid charge and discharge performance are important issues. Existing positive electrode active materials, including Patent Document 1, still have much room for improvement in reducing battery internal resistance.

[0007] A positive electrode active material for a secondary battery as one embodiment of the present invention includes: a first lithium nickel composite oxide having a particle size of 8 μm or more and 30 μm or less, and a second lithium nickel composite oxide having a particle size of 6 μm or less, the first lithium nickel composite oxide being secondary particles formed by aggregation of primary particles, and at least one selected from Ca and Sr is present on the surface of the primary particles, and the total content of Ca and Sr in the first lithium nickel composite oxide is greater than or equal to the total content of Ca and Sr in the second lithium nickel composite oxide.

[0008] As another embodiment of the present invention, a positive electrode active material for a secondary battery comprises: a first lithium nickel composite oxide having a volume-based median particle size (D50) of 8 μm or more and 30 μm or less, and a second lithium nickel composite oxide having a volume-based median particle size (D50) of 6 μm or less, wherein the first lithium nickel composite oxide is a secondary particle formed by aggregation of primary particles, and at least one selected from Ca and Sr exists on the surface of the primary particles, and the total content of Ca and Sr in the first lithium nickel composite oxide is greater than or equal to the total content of Ca and Sr in the second lithium nickel composite oxide.

[0009] The secondary battery of the present disclosure includes a positive electrode including the positive electrode active material, a negative electrode, and an electrolyte.

[0010] According to the positive electrode active material disclosed herein, the internal resistance of a secondary battery can be reduced. A secondary battery using the positive electrode active material of the present invention has low internal resistance and excellent output characteristics. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 It is a diagram schematically showing an axial cross section of a secondary battery (cylindrical battery) as an example of an embodiment. DETAILED DESCRIPTION

[0012] The present inventors have found that the internal resistance of the battery can be specifically reduced by using a first lithium nickel composite oxide having a large particle size and a second lithium nickel composite oxide having a small particle size as positive electrode active materials, and making at least one selected from Ca and Sr more present on the surface of primary particles constituting the large particles, i.e., the first lithium nickel composite oxide. It is believed that when Ca or Sr is present on the particle surface of the positive electrode active material, the reaction resistance of the positive electrode can be reduced.

[0013] Compared with small particles, large particles have a smaller specific surface area and higher interface movement resistance. Therefore, it can be considered that by making at least one selected from Ca and Sr exist more on the surface of the primary particles constituting the large particles, the resistance of the positive electrode can be efficiently and effectively reduced without damaging other properties of the positive electrode such as electronic conductivity.

[0014] Hereinafter, an embodiment of the positive electrode active material and the secondary battery using the positive electrode active material of the present disclosure will be described in detail with reference to the accompanying drawings. It should be noted that the embodiment formed by selectively combining the components of the multiple embodiments and modifications described below is also included in the scope of the present disclosure.

[0015] Hereinafter, as a secondary battery, a cylindrical battery 10 in which a wound electrode body 14 is housed in a bottomed cylindrical outer can 16 is exemplified, but the outer body of the battery is not limited to a cylindrical outer can. The secondary battery disclosed herein may be, for example, a square battery having a square outer can, a coin-shaped battery having a coin-shaped outer can, or a pouch-type battery having an outer body composed of a laminate sheet including a metal layer and a resin layer. In addition, the electrode body is not limited to a wound type, and may also be a stacked electrode body in which a plurality of positive electrodes and a plurality of negative electrodes are alternately stacked with a separator.

[0016] Figure 1 FIG. 1 is a cross-sectional view of a cylindrical battery 10 as an example of an embodiment. Figure 1 As shown, the cylindrical battery 10 includes: a wound electrode body 14, an electrolyte, and an outer can 16 that contains the electrode body 14 and the electrolyte. The electrode body 14 includes a positive electrode 11, a negative electrode 12, and a separator 13, and has a wound structure in which the positive electrode 11 and the negative electrode 12 are spirally wound with the separator 13 interposed therebetween. The outer can 16 is a metal container in a bottomed cylindrical shape with one end side open in the axial direction, and the opening of the outer can 16 is sealed by a sealing body 17. In the following, for the sake of convenience of description, the sealing body 17 side of the battery is taken as the upper side, and the bottom side of the outer can 16 is taken as the lower side.

[0017] The electrolyte is not limited to a liquid electrolyte (electrolyte), but may also be a solid electrolyte. In addition, the electrolyte may be an aqueous electrolyte, and a non-aqueous electrolyte (non-aqueous electrolyte) is used in the present embodiment. The non-aqueous electrolyte comprises: a non-aqueous solvent, and an electrolyte salt dissolved in the non-aqueous solvent. Non-aqueous solvents, for example, use esters, ethers, nitriles, amides, and mixed solvents of two or more thereof. As an example of a non-aqueous solvent, there may be mentioned: ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and mixed solvents thereof. The non-aqueous solvent may contain a halogen substituted product (e.g., fluoroethylene carbonate, etc.) in which at least a portion of the hydrogen of these solvents is replaced by a halogen atom such as fluorine. The electrolyte salt, for example, uses a lithium salt such as LiPF6.

[0018] The positive electrode 11, the negative electrode 12, and the separator 13 constituting the electrode body 14 are all strip-shaped long bodies, which are alternately stacked in the radial direction of the electrode body 14 by being spirally wound. In order to prevent the precipitation of lithium, the negative electrode 12 is formed to be one size larger than the positive electrode 11. In other words, the negative electrode 12 is formed in a manner longer than the positive electrode 11 in the length direction and the width direction. The separator 13 is formed to be at least one size larger than the positive electrode 11, for example, two sheets are arranged in a manner of sandwiching the positive electrode 11. The electrode body 14 has a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like.

[0019] Insulating plates 18 and 19 are disposed above and below the electrode body 14, respectively. Figure 1 In the example shown, the positive electrode lead 20 extends toward the sealing body 17 through the through hole of the insulating plate 18, and the negative electrode lead 21 extends toward the bottom side of the outer can 16 through the outside of the insulating plate 19. The positive electrode lead 20 is connected to the lower surface of the internal terminal plate 23 of the sealing body 17 by welding or the like, and the top plate of the sealing body 17, that is, the cover 27 electrically connected to the internal terminal plate 23, serves as the positive terminal. The negative electrode lead 21 is connected to the bottom inner surface of the outer can 16 by welding or the like, and the outer can 16 serves as the negative terminal.

[0020] A gasket 28 is provided between the outer can 16 and the sealing body 17 to ensure the airtightness inside the battery. The outer can 16 is formed with a groove portion 22 in which a part of the side portion extends inward and is used to support the sealing body 17. The groove portion 22 is preferably formed in an annular shape along the circumferential direction of the outer can 16, and supports the sealing body 17 with its upper surface. The sealing body 17 is fixed to the upper part of the outer can 16 through the groove portion 22 and the open end of the outer can 16 that tightens the sealing body 17.

[0021] The sealing body 17 has the following structure: an internal terminal plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26 and a cover body 27 are stacked in order from the electrode body 14 side. The components constituting the sealing body 17 have, for example, a disc shape or a ring shape, and the components except the insulating member 25 are electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected at their respective central parts, and an insulating member 25 is sandwiched between their respective peripheral parts. When the internal pressure of the battery rises due to abnormal heat release, the lower valve body 24 is deformed and ruptured, pushing the upper valve body 26 to the cover body 27 side, thereby blocking the current path between the lower valve body 24 and the upper valve body 26. When the internal pressure rises further, the upper valve body 26 ruptures, and the gas is discharged from the opening of the cover body 27.

[0022] Hereinafter, the positive electrode 11 , the negative electrode 12 , and the separator 13 , in particular, the positive electrode active material constituting the positive electrode 11 will be described in detail.

[0023] [positive electrode]

[0024] The positive electrode 11 has: a positive electrode core 30, and a positive electrode composite material layer 31 arranged on the positive electrode core 30. The positive electrode core 30 can be made of a foil of a metal such as aluminum that is stable within the potential range of the positive electrode 11, a thin film having the metal arranged on the surface, and the like. The positive electrode composite material layer 31 contains a positive electrode active material, a binder, and a conductive agent, and is preferably provided on both sides of the positive electrode core 30 except for the portion connected to the positive electrode lead 20. The positive electrode 11 can be manufactured, for example, as follows: a positive electrode composite material slurry containing a positive electrode active material, a binder, and a conductive agent is applied to the surface of the positive electrode core 30, and the coating is dried and then compressed to form the positive electrode composite material layer 31 on both sides of the positive electrode core 30.

[0025] As the conductive agent contained in the positive electrode composite material layer 31, carbon black such as acetylene black and Ketjen black, graphite, carbon nanotubes (CNT), carbon nanofibers, graphene and other carbon materials can be exemplified. As the binder contained in the positive electrode composite material layer 31, fluorine-containing resins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyimide, acrylic resin, polyolefin, etc. can be exemplified. In addition, these resins can be used in combination with carboxymethyl cellulose (CMC) or its salt, polyethylene oxide (PEO), etc.

[0026] As an example of an embodiment, the positive electrode active material includes: a first lithium nickel composite oxide having a particle size of 8 μm or more and 30 μm or less, and a second lithium nickel composite oxide having a particle size of 6 μm or less. As another example of an embodiment, the positive electrode active material includes: a first lithium nickel composite oxide having a volume-based median particle size (hereinafter referred to as "D50") of 8 μm or more and 30 μm or less, and a second lithium nickel composite oxide having a D50 of 6 μm or less. For example, the positive electrode active material is formed by mixing two lithium nickel composite oxides having different D50s. By using the first and second lithium nickel composite oxides, for example, the filling property of the active material in the positive electrode composite material layer 31 is improved, and the high density of the positive electrode composite material layer 31 can be achieved.

[0027] The details will be described later. The first lithium nickel composite oxide is a secondary particle formed by the aggregation of primary particles, and at least one selected from Ca and Sr exists on the surface of the primary particles. The first lithium nickel composite oxide is a secondary particle formed by the aggregation of at least 10 or more primary particles. In addition, the total content of Ca and Sr in the first lithium nickel composite oxide is greater than or equal to the total content of Ca and Sr in the second lithium nickel composite oxide. In this case, the reaction resistance of the positive electrode 11 can be efficiently and effectively reduced.

[0028] The positive electrode active material may contain other composite oxides in addition to the first and second lithium nickel composite oxides within the scope of not impairing the purpose of the present disclosure. As an example of other composite oxides, a lithium transition metal composite oxide that does not contain nickel can be cited. The positive electrode active material of this embodiment may also use the first and second lithium nickel composite oxides as main components and is substantially composed of only the first and second lithium nickel composite oxides.

[0029] In the positive electrode composite material layer 31, the first and second lithium nickel composite oxides are present in a mass ratio of 50:50, for example. The mass ratio (X) of the first and second lithium nickel composite oxides is not limited to 50:50. Specifically, the mass ratio (X) is preferably 90:10≤X≤50:50, and more preferably 80:20≤X≤60:40. When the contents of the composite oxides are different, the content of the first lithium nickel composite oxide is preferably greater than the content of the second lithium nickel composite oxide.

[0030] In this specification, the particle size of the positive active material refers to the diameter of the circumscribed circle of the particles in the cross-sectional image of the positive composite material layer 31. The cross section of the positive composite material layer 31 can be made by ion beam cross-sectional milling (CP) method, and the cross-sectional image is taken by scanning electron microscope (SEM). The average particle size can be calculated by averaging the particle sizes of any 100 particles based on the SEM image, and D50 can be used instead when the particle size distribution of the positive active material can be measured.

[0031] In this specification, D50 refers to the particle size when the cumulative frequency from the smaller particle size in the volume-based particle size distribution reaches 50%. The particle size distribution of the positive electrode active material can be measured using a laser diffraction particle size distribution measuring device (MT3000II manufactured by MicrotracBEL Co., Ltd.) and water as the dispersion medium. The positive electrode active material has, for example, the following particle size distribution: there is a first peak in the range of particle size of 8 μm or more and 30 μm or less, and there is a second peak in the range of particle size of 6 μm or less. In addition, the particle size distribution of the positive electrode active material can be measured using an image-type particle size distribution measuring device (for example, CAMSIZER X2 manufactured by MicrotracBEL Co., Ltd.) and water as the dispersion medium.

[0032] For example, a first lithium nickel composite oxide having a D50 of 8 μm or more and 30 μm or less and a second lithium nickel composite oxide having a D50 of 6 μm or less are mixed to form a positive electrode active material. In this case, the D50 of the first lithium nickel composite oxide is more preferably 10 μm or more and 25 μm or more and 12 μm or less. In addition, the D50 of the second lithium nickel composite oxide is more preferably 1 μm or more and 6 μm or less. If the D50 of the two composite oxides is within this range, it is easy to achieve high density of the positive electrode composite material layer 31.

[0033] As described above, the first lithium nickel composite oxide is a secondary particle formed by agglomeration of a plurality of primary particles. The average particle size of the primary particles constituting the first lithium nickel composite oxide is, for example, 0.02 μm or more and 1 μm or less, preferably 0.05 μm or more and 0.8 μm or less. The average particle size of the primary particles is calculated as follows: 100 primary particles are extracted by SEM image analysis of the cross section of the secondary particles, the diameter of the circumscribed circle thereof is measured, and the measured values ​​are averaged and calculated.

[0034] Similar to the first lithium nickel composite oxide, the second lithium nickel composite oxide may also be a secondary particle formed by the aggregation of multiple primary particles. In this case, the average particle size of the primary particles is smaller than, for example, the average particle size of the primary particles constituting the first lithium nickel composite oxide, and may be greater than 0.01 μm and less than 0.7 μm. Alternatively, the second lithium nickel composite oxide may also be a single primary particle or a secondary particle formed by the aggregation of more than 2 and less than 5 primary particles. In this case, the charge and discharge cycle characteristics are improved. The second lithium nickel composite oxide composed of a single primary particle is, for example, a single crystal particle.

[0035] The first and second lithium nickel composite oxides have, for example, a layered rock salt structure. Examples of the layered rock salt structure include: a layered rock salt structure belonging to the space group R-3m, a layered rock salt structure belonging to the space group C2 / m, etc. Among them, from the viewpoint of high capacity and crystal structure stability, a layered rock salt structure belonging to the space group R-3m is preferred.

[0036] The first and second lithium nickel composite oxides preferably contain Ni in an amount of 50 mol% or more relative to the total molar number of metal elements other than Li. By making the Ni content 50 mol% or more, a high-capacity battery can be obtained, and the effect of adding Ca and Sr becomes more significant. The Ni content can be 80 mol% or more, or 85 mol% or more relative to the total molar number of metal elements other than Li. The upper limit of the Ni content is, for example, 95 mol%.

[0037] The first and second lithium nickel composite oxides also preferably contain at least one selected from Mn and Co. As a suitable example of the first and second lithium nickel composite oxides, there can be cited: a lithium nickel composite oxide containing Mn; a lithium nickel composite oxide containing Mn and Co; or a lithium nickel composite oxide containing Co and Al. In the case where the composite oxide contains Co, the content of Co is preferably 1 mol% or more and 25 mol% or less, and more preferably 2 mol% or more and 7 mol% or less, relative to the total molar number of metal elements other than Li. In this case, it is possible to achieve both high capacity and high durability while suppressing material costs.

[0038] In the case where the first and second lithium nickel composite oxides contain Mn, the content of Mn is preferably 5 mol% or more and 50 mol% or less relative to the total molar number of metal elements other than Li. In the case where the content of Ni is 80 mol% or more, the content of Mn is, for example, 5 mol% or more and 20 mol% or less. In this case, it is easy to take into account both high capacity and high durability. In the case where the first and second lithium nickel composite oxides contain Al, the content of Al is, for example, 0.1 mol% or more and 7 mol% or less relative to the total molar number of metal elements other than Li.

[0039] The first lithium nickel composite oxide further contains at least one selected from Ca and Sr. The second lithium nickel composite oxide may not contain Ca and Sr, but preferably contains less Ca and Sr than the first lithium nickel composite oxide. Ca and Sr are present on the surface of the primary particles constituting the composite oxide, for example, on the surface at a higher density than inside the primary particles. Ca and Sr present on the surface of the primary particles can be confirmed by TEM-EDX and STEM-EDX.

[0040] Ca and Sr are effective in very small amounts, but the lower limit of their content is preferably 0.05 mol% relative to the total molar number of metal elements other than Li in the composite oxide. On the surface of the primary particles constituting the first and second lithium nickel composite oxides, at least one of Ca in an amount of 0.1 mol% to 0.5 mol% and Sr in an amount of 0.05 mol% to 0.3 mol% relative to the total molar number of metal elements other than Li is preferably present. In this case, the resistance of the positive electrode 11 can be efficiently and effectively reduced.

[0041] The ratio (r) of the total content of Ca and Sr in the first lithium nickel composite oxide to the total content of Ca and Sr in the second lithium nickel composite oxide is, for example, greater than 1.0 and less than 6.0 (1.0≤r≤6.0). The content of Ca and Sr in the first lithium nickel composite oxide may be the same as the content of Ca and Sr in the second lithium nickel composite oxide, but is preferably higher than the content of Ca and Sr in the second lithium nickel composite oxide. In addition, as described above, the second lithium nickel composite oxide preferably contains at least one selected from Ca and Sr at a lower content than the first lithium nickel composite oxide.

[0042] The above ratio (r) is more preferably 1.1 or more and 4.0 or less (1.1 ≤ r ≤ 4.0), and particularly preferably 1.5 or more and 3.0 or less (1.5 ≤ r ≤ 3.0). In this case, the effect of reducing the reaction resistance becomes more significant. In addition, the first and second lithium nickel composite oxides preferably contain both Ca and Sr. The total content of Ca and Sr is preferably 0.05 mol% or more and 1 mol% or less, and more preferably 0.1 mol% or more and 0.5 mol% or less relative to the total molar number of metal elements other than Li. In this case, the effect of reducing the reaction resistance becomes more significant.

[0043] When the first and second lithium nickel composite oxides contain Ca and Sr, respectively, the content of either Ca or Sr in the first lithium nickel composite oxide is preferably higher than that in the second lithium nickel composite oxide. Alternatively, the second lithium nickel composite oxide may contain Ca or Sr, and the first lithium nickel composite oxide may contain Ca and Sr.

[0044] It should be noted that the average value of the combined content of Ca and Sr in the first lithium nickel composite oxide is higher than the average value of the combined content of Ca and Sr in the second lithium nickel composite oxide. That is, the first lithium nickel composite oxide may contain particles whose combined content of Ca and Sr is lower than the average value of the combined content of Ca and Sr in the second lithium nickel composite oxide. However, the particles are in a small amount, and the proportion thereof is preferably less than 30% by mass of the first lithium nickel composite oxide, more preferably less than 20% by mass, and particularly preferably less than 10% by mass. Similarly, the second lithium nickel composite oxide may contain particles whose combined content of Ca and Sr is higher than the average value of the combined content of Ca and Sr in the first lithium nickel composite oxide.

[0045] In addition, the positive electrode active material of the present embodiment includes a lithium nickel composite oxide (referred to as "composite oxide A") having a high total content of Ca and Sr, and a lithium nickel composite oxide (referred to as "composite oxide B") having a lower total content of Ca and Sr than the composite oxide A. Furthermore, when the D50 (average particle size) of the composite oxides A and B is compared, the D50 (average particle size) of the composite oxide A is larger than the D50 (average particle size) of the composite oxide B.

[0046] The first and second lithium nickel composite oxides may contain other elements besides Li, Ni, Mn, Co, Al, Ca and Sr. Examples of other elements include: Nb, Zr, Ti, W, Si, B, S, Mg, Fe, Cu, Na, K, Ba, Mo and the like. In the case where the composite oxide contains the other elements, it is preferred to contain at least one selected from W, Mo, Ti, Nb and Zr. In this case, the effect of reducing the reaction resistance becomes more significant. The content of the other elements in the first lithium nickel composite oxide may also be higher than the content of the other elements in the second lithium nickel composite oxide. In addition, the first and second lithium nickel composite oxides contain, for example, the same type of elements as each other, but the elements contained may also be different from each other, for example, only one composite oxide contains the other elements.

[0047] At least one compound selected from the following first, second, and third compounds may be fixed to the surfaces of the primary particles constituting the first and second lithium nickel composite oxides.

[0048] First compound: a compound containing at least one selected from Ca and Sr

[0049] Second compound: a compound containing at least one selected from W, Mo, Ti, Nb and Zr

[0050] Third compound: a compound containing at least one selected from Ca and Sr and at least one selected from W, Mo, Ti, Nb and Zr

[0051] The first and second lithium nickel composite oxides have a composition formula of, for example, Li x Ni a Co b Mn c Al d Ca e Sr f M g O y(wherein, 0.8≤x≤1.2, 0.5≤a<1, 0≤b≤0.2, 0≤c≤0.5, 0≤d≤0.05, 0≤e≤0.005, 0≤f≤0.003, 1≤y≤2, a+b+c+d+e+f+g=1, at least one of e and f is greater than 0). The content of elements in the composite oxide can be measured by an inductively coupled plasma atomic emission spectrometer (ICP-AES), an electron beam microanalyzer (EPMA) or an energy dispersive X-ray analyzer (EDX).

[0052] The first and second lithium nickel composite oxides can be synthesized, for example, by mixing and sintering an oxide containing at least Ni and preferably other metal elements such as Mn, Co, and Al, a Ca raw material, an Sr raw material, and a Li raw material such as lithium hydroxide (LiOH). The sintered product is crushed and then washed with water to obtain a lithium nickel composite oxide. It should be noted that the water washing step can also be omitted. As an example of a Ca raw material, there are: Ca(OH)2, CaO, CaCO3, CaSO4, Ca(NO3)2, etc. As an example of a Sr raw material, there are: Sr(OH)2, Sr(OH)2·H2O, Sr(OH)2·8H2O, SrO, SrCO3, SrSO4, Sr(NO3)2, etc.

[0053] The molar ratio of Li in the Li raw material to the metal element (Me) in the composite oxide (Li / Me ratio) and the sintering conditions are important factors in controlling the physical properties of the composite oxide particles, including the particle size. The appropriate Li / Me ratio varies slightly depending on the composition of the mixture, and is, for example, 1.015 or more and 1.055 or less.

[0054] The sintering process of the mixture includes, for example, a first sintering process and a second sintering process at a temperature higher than that of the first sintering process. In addition, the sintering of the mixture is performed in an oxygen atmosphere, and at this time, for example, the oxygen concentration is set to 85% or more. Depending on the composition of the mixture, the first sintering temperature is slightly different, and as an example, it is 500°C or more and 680°C or less. The second sintering temperature is, for example, 700°C or more and 850°C or less. Each sintering process preferably has a temperature difference of 50°C or more.

[0055] The mixture is placed in a sintering furnace for a sintering process. The sintering process may also include a plurality of heating steps with different heating rates. For example, the temperature may be raised from room temperature to the first sintering temperature (first heating step) at a rate of 1.0°C / min or more and 5.5°C / min or less, and the temperature may be raised from the first sintering temperature to the second sintering temperature (second heating step) at a rate of 0.1°C / min or more and 3.5°C / min or less, which is slower than the first heating step. The temperature may also be maintained at the highest reaching temperature of the sintering process for a predetermined time (e.g., 1 hour or more and 10 hours or less).

[0056] Lithium nickel composite oxide can be obtained by precipitating (coprecipitating) a composite hydroxide of any particle size containing Ni and any metal element and heat treating the composite hydroxide. For the composite hydroxide, for example, it can be synthesized by stirring a metal salt solution containing Ni and any metal element (Co, Al, Mn, etc.) while dropping an alkaline solution such as sodium hydroxide and adjusting the pH to alkaline (for example, above 8.5 and below 12.5). For the particle size of the composite hydroxide, there is a tendency that the higher the pH during synthesis, the smaller the particle size. In addition, the particle size of the composite hydroxide can also be controlled by adjusting the amount of the metal salt solution added, for example, there is a tendency that the particle size increases as the amount of solution increases. The first lithium nickel composite oxide and the second lithium nickel composite oxide can be made separately by controlling the particle size of the composite hydroxide as their respective precursors.

[0057] [negative electrode]

[0058] The negative electrode 12 includes: a negative electrode core 40, and a negative electrode composite material layer 41 disposed on the negative electrode core 40. The negative electrode core 40 may be made of a foil of a metal such as copper that is stable within the potential range of the negative electrode 12, or a thin film having the metal disposed on the surface. The negative electrode composite material layer 41 includes a negative electrode active material and a binder, and is preferably disposed on both sides of the negative electrode core 40 except for the portion connected to the negative electrode lead 21. The negative electrode 12 may be manufactured, for example, as follows: a negative electrode composite material slurry including a negative electrode active material and a binder is applied to the surface of the negative electrode core 40, and the coating is dried and then compressed to form the negative electrode composite material layers 41 on both sides of the negative electrode core 40.

[0059] The negative electrode active material generally uses a carbon material that can reversibly absorb and release lithium ions. A suitable example of a carbon material is graphite, including natural graphites such as flaky graphite, block graphite, and earthy graphite; artificial graphites such as block artificial graphite (MAG) and graphitized mesophase carbon microbeads (MCMB). The negative electrode active material can use elements such as Si and Sn that alloy with Li, materials containing the elements, etc. Among them, composite materials containing Si are preferred. As a suitable example of a composite material containing Si, there can be mentioned: Si-containing materials in which fine Si phases are dispersed in SiO2 phases, silicate phases such as lithium silicate, carbon phases, or silicide phases. As the negative electrode active material, graphite and Si-containing materials can also be used in combination.

[0060] As in the case of the positive electrode 11, the binder contained in the negative electrode composite material layer 41 can also use fluororesin, PAN, polyimide, acrylic resin, polyolefin, etc., preferably styrene-butadiene rubber (SBR). In addition, the negative electrode composite material layer 41 preferably also includes CMC or its salt, polyacrylic acid (PAA) or its salt, polyvinyl alcohol (PVA), etc. Among them, it is suitable to use SBR in combination with CMC or its salt, PAA or its salt. The negative electrode composite material layer 41 may also include a conductive agent such as CNT.

[0061] [Separator]

[0062] The separator 13 may be a porous sheet having ion permeability and insulation. Specific examples of the porous sheet include microporous films, woven fabrics, nonwoven fabrics, etc. As the material of the separator 13, polyolefins such as polyethylene and polypropylene, cellulose, etc. are suitable. The separator 13 may be a single-layer structure or a multi-layer structure. In addition, a resin layer with high heat resistance such as aramid resin may be formed on the surface of the separator 13.

[0063] A filler layer containing an inorganic filler may also be formed at the interface between the separator 13 and at least one of the positive electrode 11 and the negative electrode 12. Examples of the inorganic filler include oxides containing metal elements such as Ti, Al, Si, and Mg, and phosphate compounds. The filler layer may be formed by applying a slurry containing the filler to the surface of the positive electrode 11, the negative electrode 12, or the separator 13.

[0064] Example

[0065] Hereinafter, the present disclosure will be further described by way of examples, but the present disclosure is not limited to these examples.

[0066] <Example A1>

[0067] [Synthesis of the First Lithium Nickel Composite Oxide]

[0068] A composite hydroxide containing Ni, Co, and Mn in a molar ratio of 85:5:10 is synthesized by a coprecipitation method, and a composite oxide is obtained by heat treatment at 600°C. In the synthesis of the composite hydroxide, the pH and the amount of the metal salt solution are adjusted so that the D50 of the final lithium nickel composite oxide reaches about 15μm. The oxide is mixed with calcium hydroxide and lithium hydroxide in such a way that the molar ratio (Li / Me ratio) of Li in lithium hydroxide to the metal element (Me) in the composite oxide reaches 1:1.020. The mixture is placed in a sintering furnace and sintered in two stages. During the sintering process, under an oxygen flow with an oxygen concentration of 95% (per 10cm 3 The mixture was heated from room temperature to 650°C (hereinafter referred to as the "first sintering temperature") at a heating rate of 3°C / min (hereinafter referred to as the "first heating rate"). Thereafter, the mixture was heated from 650°C to 750°C (hereinafter referred to as the "second sintering temperature") at a heating rate of 1°C / min (hereinafter referred to as the "second heating rate") and maintained at 750°C for 3 hours. The sintered product was crushed and washed with water to obtain a first lithium nickel composite oxide.

[0069] The obtained first lithium nickel composite oxide was analyzed by ICP-AES, and the result showed that the content of Ca was 0.2 mol% relative to the total amount of metal elements other than Li. In addition, the volume-based D50 of the composite oxide measured by using MT3000II manufactured by MicrotracBEL Co., Ltd. and using water as a dispersion medium was 15 μm. The SEM image confirmed that the composite oxide was a secondary particle formed by the aggregation of primary particles, and TEM-EDX confirmed that Ca existed on the surface of the primary particles.

[0070] [Synthesis of the Second Lithium Nickel Composite Oxide]

[0071] The pH and the amount of the metal salt solution during the synthesis of the composite hydroxide were adjusted so that the D50 of the lithium nickel composite oxide reached about 5 μm, and the amount of calcium hydroxide added was reduced by 50%. In addition, the second lithium nickel composite oxide was obtained by the same method as the synthesis method of the first lithium nickel composite oxide. The second lithium nickel composite oxide was analyzed by the same method as the first lithium nickel composite oxide. As a result, the content of Ca was 0.10 mol% relative to the total amount of metal elements other than Li, and the volume-based D50 was 5 μm. In addition, it was confirmed that the second lithium nickel composite oxide was a secondary particle formed by the aggregation of primary particles, and by TEM-EDX, it was confirmed that Ca existed on the surface of the primary particles.

[0072] [Production of positive electrode]

[0073] As the positive electrode active material, a material obtained by mixing the above-mentioned first and second lithium nickel composite oxides in a mass ratio of 1:1 is used. The positive electrode active material, acetylene black and polyvinylidene fluoride (PVdF) are mixed in a solid content mass ratio of 95:3:2, and N-methyl-2-pyrrolidone (NMP) is used as a dispersion medium to prepare a positive electrode composite material slurry. The positive electrode composite material slurry is applied to both sides of the positive electrode core 30 formed of aluminum foil, and after the coating film is dried, the coating film is rolled with a roller and cut into a specified electrode size, thereby obtaining a positive electrode having positive electrode composite material layers 31 formed on both sides of the positive electrode core 30. It should be noted that an exposed portion where the surface of the positive electrode core 30 is exposed is provided on a part of the positive electrode.

[0074] [Production of negative electrode]

[0075] Natural graphite is used as the negative electrode active material. The negative electrode active material, sodium carboxymethyl cellulose (CMC-Na) and a dispersion of styrene-butadiene rubber (SBR) are mixed at a solid content mass ratio of 100:1:1, and water is used as a dispersion medium to prepare a negative electrode composite material slurry. The negative electrode composite material slurry is applied to both sides of a negative electrode core formed of copper foil, and after the coating film is dried, the coating film is rolled with a roller and cut into a specified electrode size to obtain a negative electrode having negative electrode composite material layers formed on both sides of the negative electrode core. It should be noted that an exposed portion where the surface of the negative electrode core is exposed is provided on a portion of the negative electrode.

[0076] [Preparation of non-aqueous electrolyte]

[0077] In a mixed solvent obtained by mixing ethylene carbonate (EC), ethyl methyl carbonate (MEC) and dimethyl carbonate (DMC) in a volume ratio of 3:3:4 (25° C.), LiPF 6 was dissolved at a concentration of 1.2 mol / L to prepare a non-aqueous electrolyte.

[0078] [Fabrication of test battery cell (non-aqueous electrolyte secondary battery)]

[0079] An aluminum lead is installed on the exposed portion of the positive electrode, and a nickel lead is installed on the exposed portion of the negative electrode, and the positive electrode and the negative electrode are spirally wound with a polyolefin separator interposed therebetween to prepare a wound electrode body. The electrode body is housed in a bottomed cylindrical outer can, and after the nonaqueous electrolyte is injected, the opening of the outer can is sealed with a sealing body to obtain a test battery cell.

[0080] <Example A2>

[0081] A test cell was prepared in the same manner as in Example A1 except that strontium hydroxide was added instead of calcium hydroxide in the synthesis of the first and second lithium nickel composite oxides so that the Sr contents were 0.15 mol % and 0.07 mol %, respectively.

[0082] <Example A3>

[0083] A test cell was prepared in the same manner as in Example A1 except that strontium hydroxide was further added during the synthesis of the first and second lithium nickel composite oxides so that the Sr contents were 0.15 mol % and 0.07 mol %, respectively.

[0084] <Example A4>

[0085] A test cell was prepared in the same manner as in Example A1 except that the amount of calcium hydroxide added was increased to adjust the Ca content to 0.20 mol % in the synthesis of the second lithium nickel composite oxide.

[0086] <Example A5>

[0087] A test cell was prepared in the same manner as in Example A2 except that the amount of strontium hydroxide added was increased to a content of Sr of 0.15 mol % in the synthesis of the second lithium nickel composite oxide.

[0088] <Example A6>

[0089] A test cell was prepared in the same manner as in Example A3 except that the amounts of calcium hydroxide and strontium hydroxide added were increased to adjust the Ca content to 0.20 mol % and the Sr content to 0.15 mol % in the synthesis of the second lithium nickel composite oxide.

[0090] <Example A7>

[0091] A test cell was produced in the same manner as in Example A1 except that calcium hydroxide was not added during the synthesis of the second lithium nickel composite oxide.

[0092] <Example A8>

[0093] In the synthesis of the second lithium nickel composite oxide, calcium hydroxide is not added, and a composition (Li 1.03 Ni 0.85 Co 0.05 Mn 0.10 KOH was added in an amount of 10 mass % of O2. Thereafter, the mixture was sintered at 750° C. for 40 hours in an oxygen flow, and a test battery cell was prepared in the same manner as in Example A1. The obtained second lithium nickel composite oxide was a single primary particle, or a particle consisting of one or more and five or less primary particles, with a volume-based D50 of 5 μm.

[0094] <Example A9>

[0095] A test cell was prepared in the same manner as in Example A1 except that niobium pentoxide was added to adjust the Nb content to 0.50 mol % during the synthesis of the first and second lithium nickel composite oxides.

[0096] <Example A10>

[0097] A test cell was prepared in the same manner as in Example A1 except that zirconium oxide was added to adjust the Zr content to 0.50 mol % during the synthesis of the first and second lithium nickel composite oxides.

[0098] <Example A11>

[0099] A test cell was prepared in the same manner as in Example A1 except that titanium oxide was added to adjust the Ti content to 0.50 mol % during the synthesis of the first and second lithium nickel composite oxides.

[0100] <Example A12>

[0101] A test cell was produced in the same manner as in Example A1 except that molybdenum oxide was added to adjust the Mo content to 0.50 mol % during the synthesis of the first and second lithium nickel composite oxides.

[0102] <Example A13>

[0103] A test cell was prepared in the same manner as in Example A1 except that tungsten oxide was added to adjust the content of W to 0.50 mol % during the synthesis of the first and second lithium nickel composite oxides.

[0104] <Comparative Example B1>

[0105] A test cell was produced in the same manner as in Example A1 except that calcium hydroxide was not added during the synthesis of the first and second lithium nickel composite oxides.

[0106] <Comparative Example B2>

[0107] A test cell was prepared in the same manner as in Example A4 except that the amount of calcium hydroxide added was reduced to adjust the Ca content to 0.10 mol % in the synthesis of the first lithium nickel composite oxide.

[0108] <Comparative Example B3>

[0109] A test cell was prepared in the same manner as in Example A5 except that the amount of strontium hydroxide added was reduced to a content of Sr of 0.07 mol % in the synthesis of the first lithium nickel composite oxide.

[0110] <Comparative Example B4>

[0111] A test cell was prepared in the same manner as in Example A6 except that the amounts of calcium hydroxide and strontium hydroxide added were reduced to 0.10 mol % and 0.07 mol % respectively in the synthesis of the second lithium nickel composite oxide.

[0112] <Comparative Example B5>

[0113] A test cell was prepared in the same manner as in Example A1 except that magnesium hydroxide was added instead of calcium hydroxide to give Mg contents of 0.20 mol % and 0.10 mol %, respectively, during the synthesis of the first and second lithium nickel composite oxides.

[0114] <Comparative Example B6>

[0115] A test cell was prepared in the same manner as in Example A1 except that barium hydroxide was added instead of calcium hydroxide in the synthesis of the first and second lithium nickel composite oxides so that the Ba contents were 0.20 mol % and 0.10 mol %, respectively.

[0116] <Examples C1 to C6>

[0117] As the raw materials of the first and second lithium nickel composite oxides, a composite oxide containing Ni, Co, and Mn at a molar ratio of 50:20:30 was used instead of a composite oxide containing Ni, Co, and Mn at a molar ratio of 85:5:10, the second sintering temperature was set to 850° C., and no water washing was performed after sintering. The composite oxides were synthesized and test cells were prepared in the same manner as in Examples A1 to A6. The physical properties of the obtained composite oxides were the same as those of the composite oxides of Examples A1 to A6.

[0118] <Examples C7 to C11>

[0119] As the raw materials of the first and second lithium nickel composite oxides, a composite oxide containing Ni, Co, and Mn at a molar ratio of 50:20:30 was used instead of a composite oxide containing Ni, Co, and Mn at a molar ratio of 85:5:10, the second sintering temperature was set to 850° C., and no water washing was performed after sintering. The composite oxides were synthesized and test cells were prepared in the same manner as in Examples A9 to A13. The physical properties of the obtained composite oxides were the same as those of the composite oxides of Examples A9 to A13.

[0120] <Comparative Examples D1 to D4>

[0121] As the raw materials for the first and second lithium nickel composite oxides, a composite oxide containing Ni, Co and Mn in a molar ratio of 50:20:30 was used instead of a composite oxide containing Ni, Co and Mn in a molar ratio of 85:5:10. The second sintering temperature was set to 850°C. No water washing was performed after sintering. Apart from this, the composite oxides were synthesized and test battery cells were made in the same manner as in Comparative Examples B1 to B4.

[0122] <Comparative Examples D5 and D6>

[0123] As the raw materials for the first and second lithium nickel composite oxides, a composite oxide containing Ni, Co and Mn in a molar ratio of 50:20:30 was used instead of a composite oxide containing Ni, Co and Mn in a molar ratio of 85:5:10. The second sintering temperature was set to 850°C. No water washing was performed after sintering. Apart from this, the composite oxides were synthesized and test battery cells were made in the same manner as in Comparative Examples B5 and B6.

[0124] The direct current resistance (DCR) of each test battery cell of the above-mentioned embodiment and comparative example was measured, and the evaluation results are shown in the table. The evaluation results shown in Table 1 are relative values ​​when the DCR value of the test battery cell of comparative example B1 is set to 100. The evaluation results shown in Table 2 are relative values ​​when the DCR value of the test battery cell of comparative example D1 is set to 100.

[0125] [Evaluation of DC resistance (DCR)]

[0126] Under a temperature environment of 25°C, the test battery cell was charged at a constant current of 0.2C until the battery cell voltage reached 4.2V, and then charged at a constant voltage of 4.2V until the current value reached 0.01C. Thereafter, the battery was discharged at a current value of 1.0C for 10 seconds, and the voltage drop caused by the discharge was measured, and the DCR was calculated using the following formula.

[0127] DCR (mΩ) = (voltage drop (mV) / current value (A))

[0128] [Table 1]

[0129]

[0130] [Table 2]

[0131]

[0132] As shown in Tables 1 and 2, the DCR of the test battery cells of the embodiments is lower than that of the test battery cells of the comparative examples, indicating that the positive electrode active material of the embodiments has an excellent resistance reduction effect. In particular, when the Ca and Sr contents of the first lithium nickel composite oxide are higher than the Ca and Sr contents of the second lithium nickel composite oxide, or when both Ca and Sr are added, the DCR reduction effect is more significant. In addition, when W, Mo, Ti, Nb or Zr is added to the lithium nickel composite oxide, a particularly excellent resistance reduction effect can be obtained.

[0133] The present disclosure will be further described by the following embodiments.

[0134] Composition 1: A positive electrode active material for a secondary battery, comprising: a first lithium nickel composite oxide having a volume-based median particle size (D50) of 8 μm or more and 30 μm or less, and a second lithium nickel composite oxide having a volume-based median particle size (D50) of 6 μm or less, wherein the first lithium nickel composite oxide is a secondary particle formed by aggregation of primary particles, and at least one selected from Ca and Sr exists on the surface of the primary particles, and the total content of Ca and Sr in the first lithium nickel composite oxide is greater than or equal to the total content of Ca and Sr in the second lithium nickel composite oxide.

[0135] Configuration 2: A positive electrode active material for a secondary battery according to Configuration 1, wherein a compound containing at least one selected from Ca, Sr, W, Mo, Ti, Nb and Zr exists on the surface of the primary particles constituting the first lithium nickel composite oxide and the second lithium nickel composite oxide.

[0136] Configuration 3: A positive electrode active material for a secondary battery according to Configuration 1 or 2, wherein on the surface of the primary particles constituting the aforementioned first lithium nickel composite oxide and the aforementioned second lithium nickel composite oxide, there is at least one of Ca in an amount of 0.1 mol% to 0.5 mol% and Sr in an amount of 0.05 mol% to 0.3 mol% relative to the total molar number of metal elements other than Li.

[0137] Configuration 4: A positive electrode active material for a secondary battery according to any one of Configurations 1 to 3, wherein the ratio (r) of the content of Ca and Sr in the first lithium nickel composite oxide to the content of Ca and Sr in the second lithium nickel composite oxide is greater than 1.0 and less than 6.0 (1.0≤r≤6.0).

[0138] Configuration 5: The positive electrode active material for a secondary battery according to any one of Configurations 1 to 4, wherein the first lithium nickel composite oxide and the second lithium nickel composite oxide further contain at least one selected from the group consisting of W, Mo, Ti, Nb and Zr.

[0139] Configuration 6: The positive electrode active material for a secondary battery according to any one of Configurations 1 to 5, wherein the second lithium nickel composite oxide is a single primary particle or a secondary particle formed by aggregation of two or more and five or less primary particles.

[0140] Configuration 7: The positive electrode active material for a secondary battery according to any one of Configurations 1 to 6, wherein the first lithium nickel composite oxide and the second lithium nickel composite oxide contain Ni in an amount of 50 mol % or more based on the total molar number of metal elements other than Li.

[0141] Configuration 8: A secondary battery comprising: a positive electrode including the positive electrode active material according to any one of Configurations 1 to 7, a negative electrode, and an electrolyte.

[0142] Description of Reference Numerals

[0143] 10 secondary battery, 11 positive electrode, 12 negative electrode, 13 separator, 14 electrode body, 16 outer can, 17 sealing body, 18, 19 insulating plate, 20 positive electrode lead, 21 negative electrode lead, 22 groove part, 23 internal terminal plate, 24 lower valve body, 25 insulating member, 26 upper valve body, 27 cover body, 28 gasket, 30 positive electrode core body, 31 positive electrode composite material layer, 40 negative electrode core body, 41 negative electrode composite material layer

Claims

1. A positive electrode active material for a secondary battery, comprising: a first lithium nickel composite oxide having a particle size of 8 μm or more and 30 μm or less, and a second lithium nickel composite oxide having a particle size of 6 μm or less, The first lithium nickel composite oxide is a secondary particle formed by aggregation of primary particles, and at least one selected from Ca and Sr exists on the surface of the primary particles. The total content of Ca and Sr in the first lithium nickel composite oxide is greater than or equal to the total content of Ca and Sr in the second lithium nickel composite oxide.

2. A positive electrode active material for a secondary battery, comprising: a first lithium nickel composite oxide having a volume-based median particle size D50 of 8 μm or more and 30 μm or less, and a second lithium nickel composite oxide having a volume-based median particle size D50 of 6 μm or less, The first lithium nickel composite oxide is a secondary particle formed by aggregation of primary particles, and at least one selected from Ca and Sr exists on the surface of the primary particles. The total content of Ca and Sr in the first lithium nickel composite oxide is greater than or equal to the total content of Ca and Sr in the second lithium nickel composite oxide.

3. The positive electrode active material for a secondary battery according to claim 1 or 2, wherein On the surfaces of the primary particles constituting the first lithium nickel composite oxide and the second lithium nickel composite oxide, at least one of Ca in an amount of 0.1 mol% to 0.5 mol% and Sr in an amount of 0.05 mol% to 0.3 mol% relative to the total molar number of metal elements other than Li exists.

4. The positive electrode active material for a secondary battery according to claim 1 or 2, wherein A ratio r of the total content of Ca and Sr in the first lithium nickel composite oxide to the total content of Ca and Sr in the second lithium nickel composite oxide is 1.0 to 6.0, that is, 1.0≤r≤6.

0.

5. The positive electrode active material for a secondary battery according to claim 1 or 2, wherein The first lithium nickel composite oxide and the second lithium nickel composite oxide further contain at least one selected from the group consisting of W, Mo, Ti, Nb, and Zr.

6. The positive electrode active material for a secondary battery according to claim 1 or 2, wherein The second lithium nickel composite oxide is a single primary particle or a secondary particle formed by aggregation of two or more and five or less primary particles.

7. The positive electrode active material for a secondary battery according to claim 1 or 2, wherein The first lithium nickel composite oxide and the second lithium nickel composite oxide contain Ni in an amount of 50 mol % or more based on the total number of moles of metal elements excluding Li. 8 . A secondary battery comprising: a positive electrode comprising the positive electrode active material according to claim 1 , a negative electrode, and an electrolyte.

Citation Information

Patent Citations

  • Positive electrode active material for nonaqueous electrolyte secondary battery and method for manufacturing the same, positive electrode for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery

    JP2018129221A